5z-0.6=6z

Simple and best practice solution for 5z-0.6=6z equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5z-0.6=6z equation:


Simplifying
5z + -0.6 = 6z

Reorder the terms:
-0.6 + 5z = 6z

Solving
-0.6 + 5z = 6z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-6z' to each side of the equation.
-0.6 + 5z + -6z = 6z + -6z

Combine like terms: 5z + -6z = -1z
-0.6 + -1z = 6z + -6z

Combine like terms: 6z + -6z = 0
-0.6 + -1z = 0

Add '0.6' to each side of the equation.
-0.6 + 0.6 + -1z = 0 + 0.6

Combine like terms: -0.6 + 0.6 = 0.0
0.0 + -1z = 0 + 0.6
-1z = 0 + 0.6

Combine like terms: 0 + 0.6 = 0.6
-1z = 0.6

Divide each side by '-1'.
z = -0.6

Simplifying
z = -0.6

See similar equations:

| -3=a(3-0)-4 | | -3u-1/3u=1/4-7/3 | | (8n-1)+(4n+5)= | | 7y(4y-2)= | | -4ac-5b= | | 2lnx-6=12 | | 3x-20x-7=0 | | x-9+x+5x=180 | | 3=a(3-0)-4 | | -2(7x-4)+6(5x+1)= | | 7x-1-9x+5= | | 4(6x-4)+5(15-3x)-4(2x+3)=-2 | | (x+3)+2x+x=23 | | 3x*3x*3x+4=31 | | 4b+-2a-c= | | 7x-1+9x+5= | | 2j-3=47 | | -18z+6=27z-20 | | y=x^2-10x+106 | | 1+3(m-8)=7-5(6m+6) | | 4+r=6r-3-6r | | 2/5(1-5)x=1/2(4x+3) | | x+1+x+2=180 | | 51-2(11y-12y)= | | f/2=f | | 7z-6=8z-4 | | 3(k-8)=5k | | x+y^2-6y+14=0 | | -13u^2-4=3u^2 | | 5x-8+2(8x+7)= | | 5=6(w-5)-19 | | 1/3v-3/2=-8/5 |

Equations solver categories